A secure and efficient access control scheme with attribute revocation and merging capabilities for fog-enabled IoT. (December 2022) - Sarma, Richa; Barbhuiya, Ferdous Ahmed
Abstract: The current era's technological innovation has accelerated the expansion of the Internet of things (IoT), leading to an exponential growth of the number of connected devices and the produced data. This inspired the emergence of fog computing paradigm that enables data processing and analysis near end-users. The cloud co-exists with fog to offer services like processing resources, huge storage, etc. But sending the data through multiple levels for analysis and storage poses a severe threat to data security in cloud-fog-IoT framework. Ciphertext-Policy Attribute-Based Encryption (CP-ABE) is a well-known cryptographic mechanism for providing fine-grained access control. However, the existing CP-ABE schemes are not suitable as they fail to address the issues of attribute merging, attribute revocation, outsourcing operations, and facilitating privileged access altogether. Hence, this paper proposes a CP-ABE scheme addressing all the aforementioned issues. Further, security and performance analyses show that the proposed scheme is secure and suitable for IoT devices. Graphical abstract: Highlights: Addresses issues: attribute merging, revocation, outsourcing, and facilitates privileged access. The resource-constrained data user needs to store only a constant size secret key. The security proof shows that it is secure against CPA Attack under DBDH assumption.